Perlindungan Konsumen terhadap Praktik Overclaim dalam Industri Skincare: perbandingan antara Indonesia dan Amerika Serikat - Anindya Putri Keisha Salsabilla; Winda Fitri; Nurlaily (Legal Standing : Jurnal Ilmu Hukum, 2026)
The rapid growth of the skincare industry, particularly through the use of digital marketing, has contributed to the increasing prevalence of overclaim practices that have the potential to mislead consumers. This study aims to examine the forms of legal protection for consumers against overclaim practices in the skincare industry in Indonesia and the United States, as well as to analyze legal principles and mechanisms that can be adopted by Indonesia to strengthen its consumer protection system. This research employs a normative legal research method using statutory, conceptual, and comparative approaches, drawing on primary and secondary legal materials, including the Consumer Protection Law, BPOM regulations, as well as the Federal Food, Drug, and Cosmetic Act and the Modernization of Cosmetics Regulation Act (MoCRA) 2022 in the United States. The findings indicate that Indonesia’s consumer protection system remains largely reactive and administrative, as supervision and law enforcement are generally conducted after products have entered the market and violations have been identified. In contrast, the United States applies a preventive and evidence-based consumer protection framework through mandatory pre-market verification, the application of the principle of scientific accountability, and the support of transparency mechanisms and class action procedures, thereby providing more effective consumer protection. These findings are consistent with Philipus M. Hadjon’s Theory of Legal Protection, which emphasizes the importance of preventive legal protection to prevent consumer harm.